2002
DOI: 10.1080/10611860290007504
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Characteristics of Calu-3 Human Bronchial Epithelial Cells: In Vitro - In Vivo Correlation to Predict Lung Absorption in Rats

Abstract: The goal of this study was to evaluate the permeability characteristics of Calu-3, human bronchial epithelial cells to passive and actively transported drugs and to correlate the data with other in vitro models and rat lung absorption in vivo. Air-interface cultured Calu-3 cells grown on collagen-coated permeable filter supports formed "tight" polarized and well differentiated cell monolayers with apical microvilli and tight-junctional complexes. Within 8-10 days, cell monolayers developed trans-epithelial ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(115 citation statements)
references
References 28 publications
8
106
0
Order By: Relevance
“…The absorption of drugs from the lungs to the systemic circulation is generally rapid, with high bioavailability for compounds with a wide range of physicochemical properties (42,43). Despite interest in lung transporters (44,45), passive diffusion appears to be the dominant mechanism.…”
Section: Dissolution Permeation Particle Clearance and Tissue Expomentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption of drugs from the lungs to the systemic circulation is generally rapid, with high bioavailability for compounds with a wide range of physicochemical properties (42,43). Despite interest in lung transporters (44,45), passive diffusion appears to be the dominant mechanism.…”
Section: Dissolution Permeation Particle Clearance and Tissue Expomentioning
confidence: 99%
“…Cell culture models of the epithelium, the principal respiratory absorption barrier, are typically used to characterize drug permeability (47). Although alternative cell lines are being developed, most studies utilize the cell types for which in vitro-in vivo relationships have been reported, namely, 16HBE14o-(48), Calu-3 cell lines (42), and primary alveolar cell cultures (49). The isolated perfused lung is an ex vivo technique which has been used to evaluate permeability in the intact lung and has been correlated with permeability in cell cultures and in vivo (50)(51)(52).…”
Section: Dissolution Permeation Particle Clearance and Tissue Expomentioning
confidence: 99%
“…These include cell lines such as the adenocarcinoma cell line Calu-3 (Shen et al, 1994) and the SV-40 transformed cell line 16HBE 14o- (Cozens et al, 1994), both of which are able to form tight junctions and polarize when grown on semi-permeable filter supports (e.g., Transwell ® inserts). The barrier properties of these cell lines have been described Forbes et al, 2003;Mathias et al, 2002) and detailed protocols for their culture, maintenance, growth and permeability assessment have been published (Meaney et al, 2002), but it should be noted that culture methods vary between laboratories, e.g., passage number, seeding density, submerged or air-liquid interface, use of extracellular matrices, media composition, duration of culture -see Forbes and Ehrhardt (2005).…”
Section: Cfdeo-/6rep-cftrmentioning
confidence: 99%
“…As for research on respiratory epithelial permeability to drugs, a correlation between the in vitro model and in vivo conditions was observed [25]. However, the correlation between in vitro model and in vivo conditions in the cytotoxicity studies is significantly less obvious.…”
Section: Discussionmentioning
confidence: 99%